0964 Introducing a Sleep Vital Sign Based on a Simple 2-Question Survey for Utilization in a Primary Care Clinic. (12th April 2019) - Arguelles, Jessica; Chang, Jeremiah; Tam, Gordon; Takehara, Joseph; Vega, Dara; Woodrum, Rosa; Han, Eugene; Asef, Mark; Becker, Kendra; Kim, Joseph B; Derose, Stephen; Hwang, Dennis
Abstract: Introduction: We introduce a sleep vital sign (SVS) based on a simple 2-question survey developed to improve recognition of patients with sleep disorders in a primary care setting and to longitudinally track sleep-related outcomes. Methods: A 2-question survey was developed: 1) "How many days a week are you NOT satisfied with your sleep?" (SVS1); 2) "How many days a week is sleepiness a problem?" (SVS2). The primary aim of the study is to determine whether implementation of the SVS in a primary clinic can improve the rate of sleep disorder diagnosis. Consecutive patients checking into the clinic were randomized to: 1) SVS group - received SVS and sleep history questionnaire that includes validated sleep surveys; 2) control group - usual care. This study reports the SVS results and compares SVS to validated sleep surveys. Comparison of diagnostic rates to control group is currently pending and not reported here. Results: N=262 patients (53.5±17.6 years; 69% women) completed the SVS and additional questionnaires. Mean SVS1 and SVS2 were 3.2±2.6 and 2.7±2.7; there were no significant differences due to age, gender, race, marital status, employment status, nor level of education. Significant incremental increases in mean scores of Epworth Sleepiness Scale–ESS (p<0.001 for both SVS1 and SVS2), Insomnia Severity Index–ISI (p<0.001), Functional Outcomes of Sleep Questionnaire 10–FOSQ10 (p<0.001), and STOP-BANG (SVS1 p=0.12, SVS2 p=0.03), were seen with each increase in SVS1 and SVS2 scores. When defining a "positive screen" if either SVS1 or SVS2 is ≥4 (or ≥3), 73% (80%) of patients with an ESS≥11 were positive for SVS, 50% (60%) of patients with a STOP-BANG≥3 were positive for SVS, and 79% (91%) of patients with an ISI≥8 were positive for SVS. Conclusion: A sleep vital sign, based on a 2-question survey, is a simple method of screening for sleep disorders in a primary care clinic. Corresponding trends in SVS scores and various validated sleep surveys were observed, supporting its potential utility as a general sleep disorder screening tool. Support (If Any): N/A